2019
DOI: 10.3390/en13010065
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Centrifugal Pump Designs and Two-Phase Flow Characteristic under Inlet Gas Entrainment Conditions

Abstract: Capability for handling entrained gas is an important design consideration for centrifugal pumps used in petroleum, chemistry, nuclear applications. An experimental evaluation on their two phase performance is presented for two centrifugal pumps working under air-water mixture fluid conditions. The geometries of the two pumps are designed for the same flow rate and shut off head coefficient with the same impeller rotational speed. Overal pump performance and unsteady pressure pulsation information are obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The pipeline characteristic is constructed according to equation (2), by placing the experimentally determined pump performance average values from 7 measurements. Value of coefficient "a" is found according to (2) for fully open valve V2, when to the operating point D correspond H0 = H, and the maximum value Q.…”
Section: Methodsmentioning
confidence: 99%
“…The pipeline characteristic is constructed according to equation (2), by placing the experimentally determined pump performance average values from 7 measurements. Value of coefficient "a" is found according to (2) for fully open valve V2, when to the operating point D correspond H0 = H, and the maximum value Q.…”
Section: Methodsmentioning
confidence: 99%
“…(6) The wall of the pump model is hydraulically smooth and without slippage. (7) The energy transfer is not considered in the simulation. The parameter settings of the numerical simulation are shown in Table 3.…”
Section: Basic Assumptions and Parameter Settingsmentioning
confidence: 99%
“…It was pointed out that the change of flow pattern of the impeller caused the pump performance to decline, especially the gas pocket in the impeller, which caused unstable pump operation. Si [7] pointed out that the accumulation of bubbles in the impeller of the centrifugal pump affects the energy exchange and transfer in the impeller, and the vortices in the impeller also intensify the accumulation of bubbles. Results showed that bubbles first gather on the suction surface of the blade, and the accumulation area diffuses to the entire impeller flow channel as the IGVF increases.…”
mentioning
confidence: 99%
“…Dupoiron (2018) reveals that the maximum bubble diameter directly influences the relative magnitude of the drag force in ESP. Si et al (2017Si et al ( , 2018Si et al ( , 2020 presented experimental and numerical results of a 3D-bladed centrifugal pump in two-phase air/water flow. A further numerical investigation of this topic was undertaken by Zhang et al (2017) to enable a pump impeller design optimization.…”
Section: Latin Symbols Bmentioning
confidence: 99%